IMPLEMENTASI CETAK PENGAJUAN TEKO DESO (CAK NGATESO) DI KABUPUBATEN JOMBANG - Dwi Hardiansyah, Ferdian Putra; Tukiman (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the implementation of a public service innovation known as Cetak Pengajuan Teko Deso (Cak Ngateso) in Sumobito Village, Jombang Regency. The innovation is a strategy by the Jombang Civil Registration Office to bring population administration services closer to village-level communities. A descriptive qualitative approach was used, guided by George C. Edwards III’s policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of the Cak Ngateso program in Sumobito Village is generally well-executed. Communication among stakeholders is effective through both formal forums and digital media. Human resources and supporting infrastructure are relatively adequate, though technical challenges such as server outages and unstable internet connections persist. The village government's disposition toward the program is highly positive, demonstrated through active commitment and involvement. The bureaucratic structure is systematically organized, with clear division of responsibilities between the Civil Registration Office and village officials. This study concludes that Cak Ngateso holds strong potential to enhance the quality and accessibility of village-based public services.